Patrones de distribución y tasas de bioerosión del erizo Centrostephanus coronatus (Diadematoida: Diadematidae), en el arrecife de Playa Blanca, Pacífico colombiano - Toro-Farmer, Gerardo; Cantera K, Jaime R.; Londoño-Cruz, Edgardo; Orozco, Carlos; Neira, Raúl (Revista de Biología Tropical, 2004)
Regular sea-urchins are one of the main bioeroding organisms affecting coral reefs around the world. The abundance, distribution and bioerosion rate of the sea-urchin Centrostephanus coronatus, were determined in different reef zones of Playa Blanca fringing reef (Gorgona Island, Colombian pacific coast) during 1997 and 1998. The erosion rates were determined calcinating the gut content of the sea-urchins to eliminate all organic components and preserve the inorganic portion of calcium carbonate. C. coronatus showed the highest densities towards the central zones of the reef (plain-crest and front) (12.4 ind/m2; range 0-48 ind/m2). The highest mean bioerosion rate was 0.103 kgCaCO3/m2/yr in the reef plain-crest (0-0.69 kgCaCO3/m2/yr). In the other zones, (back reef and reef front) the mean bioerosion rates were 0.071 (range 0-0.39) and 0.052 (range 0-0.31) kgCaCO3/m2/yr respectively. According to the present data, it can be seen that the destruction of coralline skeletons, produced in this reef by sea-urchins is rather low, compared with the abrasion caused by these organisms in other places of the world. However, the combined action of C. coronatus and other bioeroding organisms (borers and grazers), along with some adverse environmental factors to corals, can be causing a negative balance between normal processes of reef accretion-destruction in Gorgona Island reefs